Microscopic evaluation of implant platform adaptation with UCLA-type abutments: in vitro study - Rodrigues, Vinícius Anéas; Tribst, João Paulo Mendes; Santis, Leandro Ruivo De; Nishioka, Gabriela Nogueira De Melo; Lima, Dimas Renó De; Nishioka, Renato Sussumu (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
AbstractIntroduction The fit between abutment and implant is crucial to determine the longevity of implant-supported prostheses and the maintenance of peri-implant bones.Objective To evaluate the vertical misfit between different abutments in order to provide information to assist abutment selection.Material and method UCLA components (N=40) with anti-rotational system were divided as follows: components usinated in titanium (n=10) and plastic components cast proportionally in titanium (n=10), nickel-chromium-titanium-molybdenum (n=10) and nickel-chromium (n=10) alloys. All components were submitted to stereomicroscope analysis and were randomly selected for characterization by SEM.Result Data were analyzed using mean and standard deviation and subjected to ANOVA-one way, where the groups proved to statistically different (p=<0.05), followed by Tukey’s test.Conclusion The selection of material influences the value of vertical misfit. The group machined in Ti showed the lowest value while the group cast in Ni Cr showed the highest value of vertical misfit.

ResumoIntrodução O ajuste entre a prótese e o implante é fundamental para determinar a longevidade do tratamento e manutenção do osso periimplantar.Objetivo Avaliar o desajuste vertical entre diferentes infraestruturas metálicas e plataforma dos implantes, a fim de fornecer informação, para auxiliar na escolha do metal a ser utilizado.Material e método O estudo utilizou componentes do tipo UCLA (N=40), com antirrotacional, foram divididos da seguinte forma: componentes usinados em titânio (n=10), componentes fundidos em titânio (n=10), níquel-cromo-titânio-molibdênio (n=10) e em níquel-cromo (n=10). Após o torque, as amostras foram analisados em estereomicroscópio. Para caracterização em MEV, foram utilizadas as amostras mais representativas, com maior e menor desajuste vertical.Resultado Os dados foram analisados por média e desvio padrão e submetidos ao teste ANOVA ONE way, onde os grupos foram estatisticamente diferentes (p=<0,05), seguido do teste TUKEY.Conclusão A escolha do infraestrutura influencia no valor do desajuste vertical, sendo que o grupo usinado em Ti apresentou o menor valor de desajuste, e o grupo fundido em Ni Cr o grupo com maior valor de desajuste vertical.
Avaliação microscópica da adaptação da plataforma do implante com pilares protéticos do padrão UCLA: estudo in vitro
Keywords: Dental prosthesis; dental implant; Prótese dentária; implante dentário